1998
DOI: 10.1289/ehp.98106s61395
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genetic ecotoxicologic approaches to aquatic environmental bioreporting.

Abstract: Molecular and population genetic ecotoxicologic approaches are being developed for the utilization of arthropods as bioreporters of heavy metal mixtures in the environment. The explosion of knowledge in molecular biology, molecular genetics, and biotechnology provides an unparalleled opportunity to use arthropods as bioreporter organisms. Interspecific differences in aquatic arthropod populations have been previously demonstrated in response to heavy metal insult in the Arkansas River (AR) California Gulch Sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 113 publications
0
19
0
Order By: Relevance
“…Interspecific differences in aquatic arthropod populations, including reduced diversity and shifts in benthic community composition at sites located downstream from mining sites, occur in response to heavy-metal pollution (1,4,11). In addition, we previously demonstrated that the population genetic structure of Baetis tricaudatus was also perturbed in the Arkansas River in Colorado, presumably in response to impediments to gene flow in the population caused by mortality arising from exposure to pollution from heavymetal mixtures from mining sites (2). In the latter study, intraspecific differences in population structure were demonstrated using a mitochondrial 16S ribosomal DNA gene of B. tricaudatus as a measure of genetic diversity in the species in the Arkansas River.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Interspecific differences in aquatic arthropod populations, including reduced diversity and shifts in benthic community composition at sites located downstream from mining sites, occur in response to heavy-metal pollution (1,4,11). In addition, we previously demonstrated that the population genetic structure of Baetis tricaudatus was also perturbed in the Arkansas River in Colorado, presumably in response to impediments to gene flow in the population caused by mortality arising from exposure to pollution from heavymetal mixtures from mining sites (2). In the latter study, intraspecific differences in population structure were demonstrated using a mitochondrial 16S ribosomal DNA gene of B. tricaudatus as a measure of genetic diversity in the species in the Arkansas River.…”
mentioning
confidence: 96%
“…In Colorado it is estimated that heavy metals from over 5,000 abandoned waste dumps or tailing pipes impact over 2,600 km of streams (1). These hazardous waste sites expose aquatic organisms and other wildlife to multiple heavy metals as well as to other pollutants, which can exert impacts on aquatic ecosystems at different levels of organization (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Theoretically, organisms such as aquatic arthropods that experience long-term exposure to the mixtures would be most impacted by such heavy-metal pollution.…”
mentioning
confidence: 99%
See 3 more Smart Citations